2022
DOI: 10.1038/s41467-022-35156-x
|View full text |Cite
|
Sign up to set email alerts
|

Nascent peptide-induced translation discontinuation in eukaryotes impacts biased amino acid usage in proteomes

Abstract: Robust translation elongation of any given amino acid sequence is required to shape proteomes. Nevertheless, nascent peptides occasionally destabilize ribosomes, since consecutive negatively charged residues in bacterial nascent chains can stochastically induce discontinuation of translation, in a phenomenon termed intrinsic ribosome destabilization (IRD). Here, using budding yeast and a human factor-based reconstituted translation system, we show that IRD also occurs in eukaryotic translation. Nascent chains … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
8
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 10 publications
(9 citation statements)
references
References 80 publications
1
8
0
Order By: Relevance
“…Our results echo the work of the Taguchi lab, who have shown that repeats of acidic residues when polymerized by the ribosome, before the nascent peptide fills the NPET, can induce Intrinsic Ribosome Destabilization (IRD) in prokaryotes 2,3 and eukaryotes 1 . They showed that the effect of the acidic residues depends on the bulkiness of the nascent chain 2 .…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…Our results echo the work of the Taguchi lab, who have shown that repeats of acidic residues when polymerized by the ribosome, before the nascent peptide fills the NPET, can induce Intrinsic Ribosome Destabilization (IRD) in prokaryotes 2,3 and eukaryotes 1 . They showed that the effect of the acidic residues depends on the bulkiness of the nascent chain 2 .…”
Section: Discussionsupporting
confidence: 90%
“… Abstract Having multiple rounds of translation of the same mRNA is a key feature of the Central Dogma that creates substantial dynamic complexities along with opportunities for regulation related to ribosome pausing and stalling at specific sequences 15 . The molecular mechanisms controlling these critical processes and the principles guiding their evolution remain among the least understood facets of cellular physiology.…”
mentioning
confidence: 99%
“…Given the arrest-releasing activity of YheS, we aimed to investigate whether other ABCFs also play a role in coping with nascent peptide-dependent noncanonical translations. Our previous research has demonstrated that the translation of poly-acidic sequences triggers intrinsic ribosome destabilization (IRD), leading to Pth-mediated premature termination (11, 13). For instance, over 50% of the synthesized product from a model GFP mRNA containing the 20D poly-acidic sequence accumulated as Pth-sensitive peptidyl-tRNA ( Fig.…”
Section: Resultsmentioning
confidence: 99%
“…The interaction between EttA and tRNA might indeed impose constraints on the movement of the P-site tRNA, potentially leading to an inhibition of IRD. Our previous studies have shown that IRD is inhibited in situations where the dynamics of P-site tRNA is restricted by the preceding nascent chain (12, 13). Additionally, molecular simulations have indicated the possibility of P-site tRNA adopting a different positioning due to the translation of polyacidic sequence (40).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation